PERBANDINGAN RESPON GEDUNG SETBACK DAN NON-SETBACK DI BAWAH BEBAN GEMPA - Amada, Nur Maeysya Saida; Chairunnisa, Nursiah (INFO-TEKNIK, 2023)
Structure irregularities can affect a building's ability to respond to earthquakes. One of the irregular configurations often encountered is the setback structural system which is a structure with the top of the building protruding inward, causing high vertical irregularities. This study aims to determine differences in earthquakes effect between setback structural systems and non-setback structural systems by seismic response analysis. In this analysis, there are four building models with structure irregularity variations at the same conditions and location as a comparison. Model 1 is a building without vertical irregularities or non-setbacks, while the other three models are setback buildings. The building location for this analysis is Hulu Sungai Utara District in very soft soil site class (E) because the earthquake risk in this location tends to be greater than in other South Kalimantan districts. As the results of this comparative analysis based on the base shear, displacement, and drift values, the best model is model 4, which is a setback building, because the output values are smaller compared to the other three model's output. This result is due to the mass reduction in the setback building model because of vertical geometry irregularity by 150% in the x direction and 366% in the y direction.